2018
DOI: 10.21037/cdt.2018.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of pulmonary hypertension: an update

Abstract: Pulmonary hypertension (PH) is characterized by elevated pulmonary arterial pressure caused by a broad spectrum of congenital and acquired disease processes, which are currently divided into five groups based on the 2013 WHO classification. Imaging plays an important role in the evaluation and management of PH, including diagnosis, establishing etiology, quantification, prognostication and assessment of response to therapy. Multiple imaging modalities are available, including radiographs, computed tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 105 publications
0
16
0
1
Order By: Relevance
“…Cardiac magnetic resonance imaging (MRI) is a more advanced non-invasive cardiovascular imaging tool for evaluation of PH available at more specialized centers. In fact, this technology is considered the gold standard in the quantification of right ventricle volumes and function given the limitations of TTE in obtaining optimal acoustic windows in some patients [63,70]. With respect to PF patients with suspected PH, Chin et al found diastolic pulmonary arterial area as measured by magnetic resonance imaging was accurate for detection of PH (AUC 0.897) and correlated well with RHC-derived mPAP [66].…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging (MRI) is a more advanced non-invasive cardiovascular imaging tool for evaluation of PH available at more specialized centers. In fact, this technology is considered the gold standard in the quantification of right ventricle volumes and function given the limitations of TTE in obtaining optimal acoustic windows in some patients [63,70]. With respect to PF patients with suspected PH, Chin et al found diastolic pulmonary arterial area as measured by magnetic resonance imaging was accurate for detection of PH (AUC 0.897) and correlated well with RHC-derived mPAP [66].…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…Dilated RV and thickened RV wall are also suggestive of PH. RV dilation is diagnosed in axial images when RV:LV diameter is > 1, and RV hypertrophy is diagnosed when RV wall thickness is > 4 mm 60)…”
Section: Cardiac Mrimentioning
confidence: 99%
“…Con frecuencia los pacientes buscan atención médica en etapas avanzadas de la enfermedad cuando ya existe falla del ventrículo derecho (VD). 2,7,12,13 La mejor forma de realizar el tamizaje cuando se sospecha HP es mediante el ecocardiograma transtorácico (ECOTT) bidimensional con modo-M. [14][15][16] El ECOTT es una herramienta portátil, no invasiva, de relativo bajo costo, con mayor accesibilidad que el CCD y brinda múltiples parámetros confiables sobre la hemodinámica pulmonar. 17 Por ejemplo, Li et al documentaron una buena correlación entre la medición de PsAP por Eco y la PsAP medida por CCD (r = 0.794).…”
Section: Wwwmedigraphicorgmx Introducciónunclassified